Transobturator mid urethral sling surgery for stress urinary incontinence: our experience - Bettaiah, Ramesh; Saraogi, Reshu; Reddy, Chandana A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: We retrospectively evaluated the cure & improvement rate and complications incidence following transobturator approach of mid urethral sling surgery (MUS) for stress urinary incontinence (SUI). Methods: Of the total 52 patients who underwent transobturator approach of midurethral sling surgery for stress urinary incontinence at Dr. Ramesh Hospital, Bangalore, India, between January 2006 – December 2009, 48 women were available for clinical follow-up investigation. At follow-up, all 48 patients underwent a cough test, a pad test, and sonographic postvoid residual volume measurement. Women rated their subjective continence status (continent, slightly incontinent, incontinent). Objective cure was defined as a pad weight 0–1 g and a negative cough test. Results: The minimum and median follow-up was 12 months & 24 months respectively. Subjectively, 93.75 % of the patients rated themselves as continent, 2.08% as slightly incontinent, and 4.16 % as severely incontinent. The objective cure rate was 93.75%. The surgery failed in 3 patients (6.25%). 2 patients (4.16%) underwent repeat surgery. There was one case (2.08%) of vaginal erosion of mesh which required excision of the exposed part and one case (2.08%) of urinary retention requiring incision of the mesh at the center. Conclusions: Transobturator approach of mid urethral sling surgery is a safe, effective and minimally invasive procedure for SUI with a very low rate of complications.